Carboxylated nanodiamond-mediated CRISPR-Cas9 delivery of human retinoschisis mutation into human iPSCs and mouse retina. (1st January 2020) - Yang, Tien-Chun; Chang, Chia-Yu; Yarmishyn, Aliaksandr A.; Mao, Yen-Shiang; Yang, Yi-Ping; Wang, Mong-Lien; Hsu, Chih-Chien; Yang, Hsin-Yu; Hwang, De-Kuang; Chen, Shih-Jen; Tsai, Ming-Long; Lai, Yun-Hsien; et al.
Abstract: Nanodiamonds (NDs) are considered to be relatively safe carbon nanomaterials used for the transmission of DNA, proteins and drugs. The feasibility of utilizing the NDs to deliver CRISPR-Cas9 system for gene editing has not been clearly studied. Therefore, in this study, we aimed to use NDs as the carriers of CRISPR-Cas9 components designed to introduce the mutation in RS1 gene associated with X-linked retinoschisis (XLRS). ND particles with a diameter of 3 nm were functionalized by carboxylation of the surface and covalently conjugated with fluorescent mCherry protein. Two linear DNA constructs were attached to the conjugated mCherry: one encoded Cas9 endonuclease and GFP reporter, another encoded sgRNA and contained insert of HDR template designed to introduce RS1 c.625C> T mutation. Such nanoparticles were successfully delivered and internalized by human iPSCs and mouse retinas, the efficiency of internalization was significantly improved by mixing with BSA. The delivery of ND particles led to introduction of RS1 c.625C> T mutation in both human iPSCs and mouse retinas. Rs1 gene editing in mouse retinas resulted in several pathological features typical for XLRS, such as aberrant photoreceptor structure. To conclude, our ND-based CRISPR-Cas9 delivery system can be utilized as a tool for creating in vitro and in vivo disease models of XLRS. Statement of significance: X-linked retinoschisis (XLRS) is a prevalent hereditary retinal disease, which is caused by mutations in RS1 gene, whose product is important for structural organization of the retina. The recent development of genome editing techniques such as CRISPR-Cas9 significantly improved the prospects for better understanding the pathology and development of treatment for this disease. Firstly, gene editing can allow development of appropriate in vitro and in vivo disease models; secondly, CRISPR-Cas9 can be applied for gene therapy by removing the disease-causative mutation in vivo . The major prerequisite for these approaches is to develop safe and efficient CRISPR-Cas9 delivery system. In this study, we tested specifically modified nanodiamonds for such a delivery system. We were able to introduce Rs1 mutation into the mouse retina and, importantly, observed several XLRS-specific effects. Graphical abstract: Image, graphical abstract